2014
DOI: 10.1021/jp4104992
|View full text |Cite
|
Sign up to set email alerts
|

Fe K-Edge X-ray Absorption Spectroscopy Study of Nanosized Nominal Magnetite

Abstract: When studying nominal magnetite nanoparticles, it is mandatory to obtain a precise structural characterization to get an accurate relationship with their physiochemical properties. The great deal of information accumulated to date on the characterization of nominal magnetite and maghemite NPs does not clarify if the synthesized materials are single o multiphase systems involving bulk-like stoichiometric oxides (Fe 3 O 4 , γ-Fe 2 O 3 , α-Fe 2 O 3 , ...), or single or multiphase entities formed by nonstoichiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 92 publications
(145 reference statements)
15
82
0
Order By: Relevance
“…The spectra obtained for the nanoparticles under study are rather similar to the previously measured spectra of the nanoparticles synthesized without microwave assistance. 20,21 XPS Fe2p spectrum of our sample is shown in Figure 5. As one can see, the Fe2p spectrum consists of two main peaks A and C, corresponding to 2p 3/2 and 2p 1/2 states of Fe, arising from the spin-doublet splitting of 2p level.…”
Section: Toxicity Testsmentioning
confidence: 99%
“…The spectra obtained for the nanoparticles under study are rather similar to the previously measured spectra of the nanoparticles synthesized without microwave assistance. 20,21 XPS Fe2p spectrum of our sample is shown in Figure 5. As one can see, the Fe2p spectrum consists of two main peaks A and C, corresponding to 2p 3/2 and 2p 1/2 states of Fe, arising from the spin-doublet splitting of 2p level.…”
Section: Toxicity Testsmentioning
confidence: 99%
“…The corresponding X-ray absorption spectra of the host minerals are shown in Figure 2C, and those of the lamellae are shown in Figure 2D. Figure 2B shows the reference spectra of the Fe L 3,2 absorption edge of the iron oxides obtained from previous works (e.g., Kuiper et al, 1993;Pearce et al, 2006;Signorini et al, 2006;Kuzmin and Chaboy, 2014;Piquer et al, 2014). By comparing the spectral shapes of the data obtained from the present study with the references, the materials in areas 1-3 were determined to be magnetite, and those in areas 4-7 were determined to be hematite.…”
Section: Resultsmentioning
confidence: 99%
“…The cause of the little differences between the positive tetrahedral Fe 3+ and negative octahedral Fe 2+ is unknown. According to Piquer et al (2014), the shift of the energies of the absorption peaks in the magnetite XAS spectra is due to a single-phase non-stoichiometric Fe 3−δ O 4 oxide, and this modifies the structural arrangements at the Fe sites.…”
Section: Resultsmentioning
confidence: 99%
“…The edge energies of standard samples are in good agreement with literature. 22 From the figure, it is observed that the main edge of Cobalt Ferrite sample is blue shifted by about 0.6 eV, compared to that of the standard sample Fe 3 O 4 . As discussed above in the case of Co K-edge XANES spectra, the average oxidation state of Fe in the sample is more than 2.67.…”
Section: -6mentioning
confidence: 91%
“…Many authors have suggested a linear dependence of the average oxidation state on the energy positions of the absorption edge. 16,17,21,22 In Fig. 5 Fig.…”
Section: B Charge States Of Co and Fe Ionsmentioning
confidence: 99%